A dual protection strategy for stable lithium metal anodes using Ag nanoseed decorated F-doped porous graphene current collectors - Yan, Yang; Sun, Jing; Zhang, Ying; Liu, Wen; Wang, Yu-jie; Yang, Hui-qin; Li, Cheng-jie; Zhang, Juan (Inorganic chemistry frontiers, 2023)
Lithium metal batteries have been regarded as typical representatives of high-energy storage systems. However, lithium dendrite growth and a fragile solid electrolyte interface (SEI) lead to safety issues and unsatisfactory performances. We tackle the above issues with a dual protection strategy by designing a silver (Ag) decorated F-doped graphene (Ag@FG) matrix. Ag@FG was synthesized by a one-step "ion atmosphere" method. When used as a current collector, Ag@FG shows a low nucleation overpotential and a long cycle life due to the enhanced lithiophilicity, high conductivity of the matrix, and the LiF-enriched SEI. The decorated Ag nanoparticles increased the lithiophilicity of the graphene matrix to induce the uniform deposition of lithium. The doped F leads to the formation of a stable SEI. Thus, Ag@FG shows a low nucleation overpotential of only 8 mV at 0.5 mA cm −2 and long-term stability for over 1600 h at 1.0 mA cm −2 and 1.0 mA h cm −2 . The assembled full batteries with LFP also indicate its practicability with good cycling stability and rate capability. A dual protection strategy is proposed by fabricating a Ag decorated F-doped graphene (Ag@FG) current collector. The decorated Ag induces the uniform deposition of Li and F doping facilitates the formation of a stable LiF-enriched SEI.